Spectral analysis of the topography parameters for isotropic Gaussian rough surfaces applied to gold coating. (January 2022) - Najah, Mohamed; Maaboudallah, Farouk; Boucherit, Mohamed; Ferguson, Mark; Fréchette, Luc; Charlebois, Serge; Boone, François; Ecoffey, Serge
Abstract: In the fabrication of microelectronic devices, sputtering of thin films leads to isotropic rough surfaces described by (i) a Gaussian height distribution and (ii) a constant power spectral density (PSD) up to a roll-off frequency of q 0 from which it decays as a power law. This paper introduces a robust approach to estimate the topography parameters such as the density, the mean radius of curvature and the height distribution of summits for isotropic Gaussian rough micro-surfaces. The proposed approach consists of computing the PSD function from the atomic force microscopy measurements, approximating the value of q 0 and the magnitude P 0 of the plateau by curve fitting algorithms, and analytically deriving the topography parameters using the random process theory. The robustness of the proposed methodology is assessed on a sputtered gold micro-surface. The investigations show that the proposed PSD-based approach reduces the dependence of the topography parameters on the sampling length compared to the deterministic method. Moreover, the PSD-based estimated density of summits is in a good agreement with scanning electron microscopy analysis, in contrast to both deterministic and autocorrelation-based methods. The proposed approach is therefore more suitable to extract topography parameters from measurements of micro-surfaces for the development of contact asperity-based models. Highlights: Power spectral analysis of gold micro-surface. Statistical estimation of the density, radius of curvature and height distribution of summits from sputtered gold. Reduction of the sensitivity of the topography parameters to the measurement resolution.